Variations in tuberculin sensitivity in tuberculous children after treatment - Yalçın, R. Cengiz; Dolgin, Joseph (The Turkish Journal of Pediatrics, 1963)
This study was made of 131 children between four months and 13 years of age, all of whom were treated for periods of time ranging from four months to two and a half years. During this period we used INH alone on a group of 98 children and more than one agent (INH - PAS, INH - Strep., and INH - PAS - Strep.) on 33 patients. We observed that 60 per cent of our patients showed a decrease in tuberculin reaction after INH treatment and that 42 per cent of those who received the combined treatment showed a decreased reaction. Only two children became negative at the end of the test.